Pelatihan Pemanfaatan Teknologi Multimedia Untuk Membuat Media Pembelajaran - Agus Priyadi; Ahmad Zainudin; Andik Prakasa Hadi; Rudjiono Rudjiono; Setiyo Adi Nugroho; Priyadi Priyadi; Robby Andika Kusumajaya; Danang Danang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The results of observations, efforts to improve the quality of education, SDIP Haji Muhammad Subandi need tools or media to convey lessons as a substitute for teaching aids, describe an incident, and provide examples. Computers and projectors are only used to display text using Microsoft Word and Power Point application software. Animation, sound and video are never used. Multimedia has many variations in appearance so that learning activities become more interesting, effective and efficient. The development of multimedia technology, one of which is the website, provides many tools for making various media such as images, converters, sound, animation, and video, which can be used to facilitate the creation of multimedia-based learning media. Canva on its website mentions its mission so that people can design and publish anywhere and anytime. This training was held for teachers at SDIP Haji Muhammad Subandi so that teachers have additional knowledge and alternative options for teaching students using Canva's easy-to-use and complete tools..